CD105/Ki67 double immunostaining expression in liver metastasis from colon carcinoma - Ceauşu, Raluca Amalia; Cîmpean, Anca Maria; Gaje, Puşa; Gurzu, Simona; Jung, I; Raica, M (Romanian journal of morphology and embryology, 2011)
The liver is the most common and critical site for the development of colon cancer metastases. Tumor angiogenesis in liver metastasis from colon carcinoma is a controversial subject. Liver microenvironment, immunophenotypical and morphological particularities of hepatic vessels are only few aspects, which establish difficulties in quantification of tumor vascularisation from liver metastasis. The aim of this work is to study the distribution of CD105 positive vessels and the proliferation rate of endothelial cells from liver metastasis of colon carcinoma based on double immunostaining CD105/Ki67. In liver metastasis from well-differentiated adenocarcinoma we found a high number of CD105+/Ki67- vessels. On the other hand, in liver metastasis from poorly differentiated adenocarcinoma we noticed rare CD105+/Ki67+ vessels. It is hypothesized that neoangiogenesis of liver metastasis is performed through intussusceptive mechanism rather than sprouting and could be supported by the presence of kissing phenomenon, CD105 positive transcapillary pillars and the absence of endothelial cells proliferation in this vessels. We conclude that in liver metastasis principal mechanism of neovascularisation formation is based on intussusception.